2018
DOI: 10.1002/art.40398
|View full text |Cite
|
Sign up to set email alerts
|

Review: Transcriptional Regulation of CD4+ T Cell Differentiation in Experimentally Induced Arthritis and Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disorder characterized by chronic inflammation of the joint synovium and infiltration by activated inflammatory cells. CD4+ T cells form a large proportion of the inflammatory cells invading the synovial tissue, and are involved in the RA pathologic process. In general, CD4+ T cells differentiate into various T helper cell subsets and acquire the functional properties to respond to specific pathogens, and also mediate some autoimmune disorders such as RA. Because the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 86 publications
1
74
0
Order By: Relevance
“…Accordingly, Th17 cells, which not only elicited synovial inflammation and pannus formation, but also promoted articular cartilage and bone destruction, have been implicated in RA. In addition, distinct effector subsets of CD4 + Th cells were also involved in the pathology of RA . Hence, further studies on the interaction between Th17 and other Th cells contributed to revealing the immunologic mechanism of RA.…”
Section: The Function Of Th17 Cells On Ramentioning
confidence: 99%
“…Accordingly, Th17 cells, which not only elicited synovial inflammation and pannus formation, but also promoted articular cartilage and bone destruction, have been implicated in RA. In addition, distinct effector subsets of CD4 + Th cells were also involved in the pathology of RA . Hence, further studies on the interaction between Th17 and other Th cells contributed to revealing the immunologic mechanism of RA.…”
Section: The Function Of Th17 Cells On Ramentioning
confidence: 99%
“…Helper T cells (cluster of differentiation [CD] 4 + T cells) are important elements in adaptive immune systems and can be divided into several subtypes [6]. In in amed RA synovium, CD4 + T cells are predominant [7], suggesting that CD4 + T cells may be cornerstone immune cells in RA pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Type 17 helper T cells (Th17 cells) have been identi ed in RA [8,9], and before identifying Th17 cells, interferon (IFN)-γ-secreting Th1 cells have been thought as major pathologic cells in RA development [10]. IFN-γ is the main cytokine produced by Th1 cells [6], and autoreactive Th1 cells are increased in the peripheral blood and synovial uid of patients with RA [11,12]. However, the effects of IFN-γ in animal models are unclear [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The study of the regulatory architecture of cells has revealed numerous examples of co-regulation of transcription of large numbers of genes (Jang et al, 2017;Kondo et al, 2018), and this has been used to link the organization of cells to their distinct functions in response to developmental or external stimuli (Romero et al, 2012). While studies of cells in bulk have led to interesting population-level insights about the relationships between genes (Thompson et al, 2015), the study of individual cells via single-cell RNA-seq has led to questions about how the relationships between genes depend on cell type (Lindgren et al, 2017).…”
Section: Introductionmentioning
confidence: 99%